A Novel Ritonavir Paediatric Powder Formulation is Bioequivalent to Ritonavir Oral Solution with a Similar Food Effect. Issue 4 (May 2015) - Salem, Ahmed Hamed; Chiu, Yi-Lin; Valdes, Joaquin M; Nilius, Angela M; Klein, Cheri E
Background: A novel ritonavir oral powder formulation has been developed to eliminate the alcohol and propylene glycol contents in the current ritonavir oral solution for paediatric use. Two clinical studies were conducted to assess the bioequivalence of the powder formulation to the marketed oral solution and to evaluate the effect of food and vehicles on bioavailability. Methods: Study 1 was a randomized, partial-crossover, 4-period study in 48 subjects. Regimens included: oral solution under moderate-fat conditions, powder formulation in water under fasting, moderate-fat or high-fat conditions, and powder formulation in chocolate milk or pudding under moderate-fat conditions. Study 2 was a randomized, crossover, 4-period study in 24 subjects. Subjects were randomized to a sequence of the oral solution and powder formulation in water, infant formula and apple sauce, all under moderate-fat conditions. Bioavailability comparisons were assessed by the 90% CIs for the geometric least-squares mean ratios. Results: Ritonavir powder formulation in water was found to be bioequivalent to the marketed oral solution. Ritonavir powder formulation administered in chocolate milk, pudding, infant formula or apple sauce was bio-equivalent to the powder formulation administered in water. Compared with fasting conditions, moderate-fat and high-fat meals were associated with approximately 25–40% and 35–50% reduction in ritonavir concentrations, respectively. Conclusions: The novel ritonavir powder formulation is bioequivalent to marketed ritonavir oral solution under moderate-fat conditions with a similar effect of meals. None of the vehicles tested negatively affected the bioavailability, which suggests the potential for use of a broad range of vehicles for dose preparation.